Low-temperature growth of zinc oxide structures on flexible conductive substrate: effect of NaOH and C7H8O9 presence in solgel - Kamardin, Ili Liyana Khairunnisa (2021)
ZnO is a unique material that exhibits semiconducting, piezoelectric, and pyroelectric multiple properties. ZnO nanostructures have drawn a widespread interest from researchers because of their multi-functional properties. The purposes of this study are to investigate the effects of adding sodium hydroxide and citric acid in the basic sol-gel on the formation of zinc oxide (ZnO) nanostructures via a chemical method. A ZnO sol was prepared by dissolving zinc acetate dehydrate (ZnAC) and diethanolamine (DEA) in deionized water (H2O) and isopropanol (2-PrOH). The precursor solutions were spin-coated on the ITO/PET substrate and were dried at room temperature and pre-heated oven at 150°C for 3 minutes. Hot Water Treatment (HWT) was carried out at 70°C, 80°C, and 90°C for 8, 12, and 16 hours. X-ray diffraction (XRD) analysis recorded that (100) and (101) planes were formed as the preferred orientation samples with good quality and crystallization of the ZnO thin films. Based on Atomic Force Microscope (AFM) and Field Emission Scanning Electron Microscope (FESEM), HWT of 12 h immersed time was noticed as the optimum time for the growth of ZnO structures with the basic sol-gel solution. A 0.75 mol of NaOH and C6H8O7, respectively, was dropped in the basic solution for the second part of this study. The HWT was carried out at 90°C for 8, 12, and 16 hours. The presence of NaOH recorded higher intensity with ZnO sheet structure in a flower bud shape. The size of the structures approached nano-size. The presence of NaOH and C6H8O7 has changed the ZnO dimension from 1D to 2D. The ZnO 1D rod structures and 2D sheet structures can be used in LED, solar cells, photodetectors, gas sensor, field emitter, and photovoltaic devices.